Ac-Susceptibility of Granular Superconductors - Salamati, Hadi (Universiti Putra Malaysia Press, 1998)
The real and imaginary parts of ac-susceptibility of sintered Y Ba2 CU3 Ox and (BiJ.6 PbO.2 SbO.2) Sr2 Ca2 CU3 Ox superconductors were measured before and after powdering. The temperature-dependent susceptibility may be separated into two contributions, one sensitive and the other relatively insensitive to the magnitude of the measuring field. The former is partially suppressed by coarsely crushing the sample. It is completely suppressed after finely powdering. Some of the models apparently consistent with the results are discussed.